2012
DOI: 10.1029/2012jc007923
|View full text |Cite
|
Sign up to set email alerts
|

Rogue waves in crossing seas: The Louis Majesty accident

Abstract: [1] We analyze the sea state conditions during which the accident of the cruise ship Louis Majesty took place. The ship was hit by a large wave that destroyed some windows at deck number five and caused two fatalities. Using the wave model (WAM), driven by the Consortium for Small-Scale Modelling (COSMO-ME) winds, we perform a detailed hindcast of the local wave conditions. The results reveal the presence of two comparable wave systems characterized almost by the same frequency. We discuss such sea state condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 34 publications
4
70
1
2
Order By: Relevance
“…The "old" wind sea was transformed into a young swell, which led to a marked decrease in D. The closer wave period and narrower direction angle between the wind sea and the swell produced a resonance effect. Some experimental studies suggest that a swell with the same direction as the wind will play a role in suppressing the growth of a wind sea (Philips and Banner, 1974;DoneJan, 1987). As the swell direction tends to be the same as the wind direction, the development of a wind sea is suppressed.…”
Section: Sea States Of Typical Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…The "old" wind sea was transformed into a young swell, which led to a marked decrease in D. The closer wave period and narrower direction angle between the wind sea and the swell produced a resonance effect. Some experimental studies suggest that a swell with the same direction as the wind will play a role in suppressing the growth of a wind sea (Philips and Banner, 1974;DoneJan, 1987). As the swell direction tends to be the same as the wind direction, the development of a wind sea is suppressed.…”
Section: Sea States Of Typical Casesmentioning
confidence: 99%
“…A sea state with a narrow wave spectrum was observed during several major ship accidents, including the Voyager accident (Bertotti and Cavaleri, 2008), the Suwa Maru incident (Tamura et al, 2009), the Louis Majesty accident (Cavaleri et al, 2012) and the Onomichi Maru incident Waseda et al, 2014). Studies have assumed that the narrowed wave spectrum is primarily generated by the nonlinear coupling of swell and wind sea (or swell and swell) (Bertotti and Cavaleri, 2008;Tamura et al, 2009;Cavaleri et al, 2012;Waseda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamura et al (2009) demonstrated that the wind-sea energy of a studied complex wave field contributed to the exponential growth of the swell system, generating a unimodal "freakish" sea. Cavaleri et al (2012) analysed the sea state conditions at the time of the accident with the Louis Majesty cruiser characterized by the coexistence of two wave systems of comparable energies and peak periods, propagating at 40-60 • . Furthermore, the possible rogue wave conditions at the time of the accident have been successfully, though qualitatively, modelled using a system of two coupled nonlinear Shrödinger equations.…”
Section: P G Petrova and C Guedes Soares: Distributions Of Nonlinementioning
confidence: 99%
“…A major challenge is to predict them and, if possible, to control them, making safer environments and systems. In oceanography, ultrahigh waves, referred to as rogue waves (RWs), have been extensively studied [1][2][3][4], and they have also been observed in many other systems [5][6][7][8]. Rogue waves, as opposed to tsunamis or solitons, can disappear in a short spatial length and not necessarily propagate for large distances.…”
Section: Introductionmentioning
confidence: 99%